2023
DOI: 10.1111/papr.13214
|View full text |Cite
|
Sign up to set email alerts
|

Mapping guideline‐informed care for chronic non‐specific low back pain with the biopsychosocial approach: A rapid review

Abstract: Background Current evidence favors a multidisciplinary biopsychosocial approach to the management of chronic non‐specific low back pain (CLBP). However, it is unclear whether such an approach is facilitated by current clinical guidelines. This rapid review set out to examine the extent to which clinical guideline recommendations for managing CLBP address domains of the biopsychosocial approach. Methods MEDLINE, EMBASE, CINAHL, and the gray literature were searched for any clinical guidelines targeting the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This finding aligns with a recent rapid review on informed care for chronic NSLBP utilizing a biopsychosocial approach, which found that only 53% (8 out of 15) of the guidelines addressed all three domains of the biopsychosocial approach. 34 In future CPGs for the management of patients with NSLBP, it is anticipated that greater emphasis should be placed on psychological and social aspects alongside biological factors to enhance the biopsychosocial approach. This assertion is supported by a recent metaanalysis, which concluded that biopsychosocial interventions yielded superior outcomes compared to solely engaging in active physiotherapy management for patients with chronic NSLBP.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a recent rapid review on informed care for chronic NSLBP utilizing a biopsychosocial approach, which found that only 53% (8 out of 15) of the guidelines addressed all three domains of the biopsychosocial approach. 34 In future CPGs for the management of patients with NSLBP, it is anticipated that greater emphasis should be placed on psychological and social aspects alongside biological factors to enhance the biopsychosocial approach. This assertion is supported by a recent metaanalysis, which concluded that biopsychosocial interventions yielded superior outcomes compared to solely engaging in active physiotherapy management for patients with chronic NSLBP.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The chronicity of non-specific LBP has been suggested to be due in part to psychosocial factors. 10 , 11 Previous studies have shown that fear-avoidance beliefs and kinesiophobia, as assessed by the physical activity subscale of the Fear-Avoidance Beliefs Questionnaire (FABQ-PA) and the Tampa Scale for Kinesiophobia (TSK)-11 scores, are significantly associated with presence of CLBP. 12 , 13 Although several investigations have shown an association CLBP and psychosocial factors in workers, 12 , 13 few similar studies have been conducted in athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Engel [ 15 ] theorised the biopsychosocial model and described how the interconnection between biological, psychological, and social factors influenced mental health. The biopsychosocial model comprises three domains—the biological domain (e.g., age, biomechanics, comorbidity, gender, genetics, metabolic factors, neurochemistry, pathophysiology, and physical), the psychological domain (e.g., addictions, attitudes/beliefs, cognitive factors, developmental issues, expectations, literacy/health literacy, mental illness, past experiences, personality, preferences, psychological stress, readiness to change, self-efficacy, and self-esteem), and the social domain (e.g., economic factors, employment/occupation, environment/geography, ethnicity/culture/race, family/social support and relationships, health provider/system factors, housing, and language proficiency) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%